The law of Establishing the Supreme Authority for Transparency, Preventing and Fighting against Corruption 08-22 What is the change? And what for? - Haltali, Ahmed (Journal of Legal Studies and Researches, 2023)
This article comes to consider the extent of change and the feasibility of changing a national authority to prevent and combat corruption to a higher authority for transparency and preventing and combating corruption.